Social media tools as an instrument of modern political engagement – the attitudes of students in Serbia - Obradović, Neven D.; Atlagić, Siniša (Sociološki pregled, 2021)
In this paper, the authors present the research results about the attitudes of the student population in Serbia regarding the use of social media tools as instruments of political engagement. The text presents a segment of a broader study of political communication of young people in Serbia, conducted within the benefit concept. The research results show that social media tools do not contribute to the political engagement of young people in online sphere. The authors interpret the results in the context of political communication and power, indicating the absence of efforts by young people in Serbia to acquire political subjectivity and persuasive action in the environment.